Assessment of the validity of the English National Health Service Adult In-Patient Survey for use within individual specialties. Issue 8 (21st May 2013) - Sullivan, P J; Harris, M L; Doyle, C; Bell, D
Abstract : Background: Healthcare improvement requires rigorous measurement. Patient experience is a key healthcare outcome and target for improvement. Its measurement requires psychometrically validated questionnaires. In England, the Adult In-Patient Survey (AIPS), which is validated for use across the entire acute inpatient population, is administered to unselected patients after discharge from National Health Service acute Trusts. The AIPS is reported at an organisational level, but subhospital level data are needed for local quality improvement; it is currently uncertain whether the AIPS retains validity in local specialty subgroups. Methods: We analysed the results of AIPS for 2010 (n=56 931 returns) by specialty (medicine, surgery, orthopaedics, renal medicine, neurosurgery, obstetrics-gynaecology and oncology) to determine whether validity is retained at a suborganisational level. Results: Criterion validity and internal consistency of AIPS were retained for most specialty subgroups. When small local samples were excluded, the results for Trust level specialty groups were similar over a 2-year period, indicating test stability. For oncology there was poor internal consistency in the 'doctors' domain and criterion validity, expressed as the relationship elements of experience and overall rating of care, was less than for other specialties. Conclusions: The AIPS is suitable for use within many specialties, but our findings question some elements of validity for oncology inpatients. We recommend that future surveys are administered and reported by specialty, to inform local improvement and permit comparison of specialty units.